2017
DOI: 10.1186/s12864-017-4204-6
|View full text |Cite
|
Sign up to set email alerts
|

Institute collection and analysis of Nanobodies (iCAN): a comprehensive database and analysis platform for nanobodies

Abstract: BackgroundNanobodies are single-domain antibodies that contain the unique structural and functional properties of naturally-occurring heavy chain in camelidae. As a novel class of antibody, they show many advantages compared with traditional antibodies such as smaller size, higher stability, improved specificity, more easily expressed in microorganisms. These unusual hallmarks make them as promising tools in basic research and clinical practice. Although thousands of nanobodies are known to be published, no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In their 2017 study, Zuo and co-workers (Zuo et al, 2017) found more than 2,300 sequences of V H H domains, but 90% in patents and only 74% in PDB structures. With the availability of huge numbers of V H H sequences in the large majority of the proteins, it is interesting and essential to predict models of V H H domains, to understand their binding and specific properties.…”
Section: Introductionmentioning
confidence: 99%
“…In their 2017 study, Zuo and co-workers (Zuo et al, 2017) found more than 2,300 sequences of V H H domains, but 90% in patents and only 74% in PDB structures. With the availability of huge numbers of V H H sequences in the large majority of the proteins, it is interesting and essential to predict models of V H H domains, to understand their binding and specific properties.…”
Section: Introductionmentioning
confidence: 99%
“…As nanobodies are single-chain-binding units, small, and to be generated against any possible target, the nanobody is currently the preferred binding unit. Moreover, given the versatility of nanobody applications (Beghein and Gettemans 2017 ) and recent establishment of a centralized nanobody database collection (ICAN; Zuo et al 2017 ), the expansion of the FLIPPER-bodies has great promise. However, alternative small, single-domain-binding scaffolds capable of binding with high affinity to their target such as affibodies may also be employed in the FLIPPER-body technology (Helma et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Validated nanobody sequences can be found in publicly available protein or Nb-specific databases (Zuo et al, 2017), shared upon request from lab groups, or can be purchased as plasmids from Addgene or individual companies (Appendix). …”
Section: General Protocols For Nanobody Generation Recombinant Evolumentioning
confidence: 99%
“…iCAN (Institute Collection and Analysis of Nanobody): http://ican.ils.seu.edu.cn/Home/Index/can (Zuo et al, 2017) Over 100,000 freely accessible sequences as of August 2018Searchable though keywords (i.e., GFP, actin)Video tutorial for searching and adding to the databaseDownloadable search results include Available DNA and protein sequencesRelated publications (PubMed ID)Source organism and experimental methods of screeningFunction (i.e., crystallization or imaging)Patent information…”
Section: Resources For Nb Derivation and Fusion Protein Cloningmentioning
confidence: 99%